2018
DOI: 10.2174/1874210601812011043
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Peripheral Giant Cell Granuloma: A Case Report

Abstract: Objective: This article describes a case of a Peripheral Giant Cell Granuloma (PGCG) in a girl. Introduction: PGCG is a relatively infrequent benign reactive lesion of the gingiva or alveolar ridge that develops in response to local irritation. Clinical appearance consists of a firm or soft smooth surface nodule in dissimilar colors of varying size with sessile or pedunculated implantation base. Radiographic features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…It is a benign hyperplasic lesion but not a true neoplasm. [ 3 4 5 ] Palacios et al . suggested that the origin of giant cells in this lesion by the fusion of histiocytes, endothelial cells, pericytes, and fibroblasts gives rise to giant cell formation, but the source of giant cells origin has still been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…It is a benign hyperplasic lesion but not a true neoplasm. [ 3 4 5 ] Palacios et al . suggested that the origin of giant cells in this lesion by the fusion of histiocytes, endothelial cells, pericytes, and fibroblasts gives rise to giant cell formation, but the source of giant cells origin has still been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Uma multiplicidade de fatores intervenientes ao teletrabalho têm sido apontados na literatura (Anderson;Kaplan;Vega, 2014;Tremblay;Thomsin, 2012;Chakrabarti, 2018;Barros;Silva, 2010;Caillier, 2016;Choi, 2018), desde possibilidade de equilíbrio entre vida pessoal e profissional, redução de custos ao empregador e diminuição de congestionamento do trânsito. Destacando-se a qualidade de vida dos teletrabalhadores.…”
Section: Figura 3 -Motivos Para a Não Recomendação Da Gam E Gagro Pel...unclassified
“…O teletrabalho é caracterizado como inovação organizacional e configura uma alternativa estratégica às mudanças que estão ocorrendo no processo de trabalho, mesmo que não exista uniformidade de opiniões relacionadas aos efeitos dessa prática para as empresas, para o empregado e nem para a sociedade (Barros;Silva, 2010). Ordoñez (2012, p. 189) afirma que o teletrabalho "gera importantes transformações no indivíduo, redefinindo conceitos-chave como tempo, lugar, vida familiar e, em geral, vida social".…”
Section: Referencial Teórico 21 Teletrabalhounclassified
See 2 more Smart Citations